Korelasi tingkat pendapatan orang tua terhadap prestasi belajar matematika siswa kelas VI sekolah dasar - Cindy Ineke Ferdianti; Erika Yolanda Friselya; Mohammad Edy Nurtamam (Jurnal Pendidikan Dasar, 2025)
This study aims to analyze the correlation between parental income and mathematics learning achievement of grade VI students at SDN Banyuajuh 3 Kamal. The approach used is quantitative descriptive with simple random sampling method, involving 27 students as samples. Data on parental income were collected through questionnaires, while data on mathematics learning achievement were obtained from class teachers. Correlation tests were conducted using SPSS software to determine the relationship between the two variables. The results of the analysis showed that there was no significant correlation between parental income and students' mathematics learning achievement, with a correlation coefficient value of -0.112 and a significance of 0.579 (greater than 0.05). Although parental income can provide access to educational facilities, other factors such as student motivation, teaching quality, family support, emotional and social intelligence, and a conducive social environment, play an important role in determining academic achievement. Therefore, to improve student achievement, a more holistic approach is needed that takes into account these various factors.